Computational study of heat transfer in honeycomb structures accounting for gaseous pore filler - Vesenjak, Matej (Scitec Publications Ltd., 2008)
Thermal properties of honeycomb structures with different cell shapes are investigated in this paper. The influence of cell shape, relative density and pore gases on the macroscopic honeycomb thermal properties is investigated by means of transient dynamic computational simulations. The ANSYS CFX code is used to evaluate the heat conduction trough the base material and the filler gas, as well as the convection in gas filler. The computational results clearly show a strong influence of the filler gas on heat conduction and macroscopic thermal properties of analyzed honeycomb structures, which is attributed to low relative density of the cellular structure. Additionally, the influence of considered relative densities is more prominent than the influence of cell shape. The evaluated results are valuable for further development of homogenization models of heat transfer in honeycomb structures accounting for gaseous pore fillers.